Pathology and VP2-Based Characterization of Infectious Bursal Disease Virus Associated with an Outbreak in Layer Chickens in Ghana - Ben Enyetornye; Henry A. Abugri; Ama K. Kusi-Appiah; Grazieli Maboni; Theophilus Odoom; Nicole L. Gottdenker; Binu T. Velayudhan (Pathogens)
Infectious bursal disease (IBD) continues to threaten poultry production globally, with highly virulent strains circulating in many parts of Africa. In this study, molecular characterization was performed on a circulating infectious bursal disease virus (IBDV) strain from an outbreak in a layer flock in Ghana. Layer chicks presented for necropsy had markedly enlarged and hemorrhagic bursae of Fabricius, with necrotic foci and catarrhal exudate on the serosal surface. Histopathology of the bursa of Fabricius revealed scattered to effacing hemorrhages on the plicae, extensive necrosis with expansion of the stroma between the follicles, and depletion of lymphocytes within the interfollicular epithelium. Reverse transcription polymerase chain reaction (RT-PCR) and subsequent sequencing of the VP2 gene showed the presence of IBDV in formalin-fixed paraffin-embedded tissues. A phylogenetic analysis compared 62 other IBDV sequences from different parts of the world and placed the Ghanaian IBDV in genogroup 3 (vvIBDV), closely related to IBDV from Nigeria. In comparison to reference vvIBDV, there were amino acid substitutions at positions 252, 254, and 300. To the best of our knowledge, this is the first report in which an IBDV from a disease outbreak in Ghana has been sequenced and compared with other IBDVs in a phylogenetic analysis.